Penggunaan Ragam Kata Sapaan di Pondok Pesantren Putri Walisongo Jombang: Kajian Sosiolinguistik - Putri Nita; Andika Herma Putra (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2022)
Language is a tool in communicating. Without language we will not be able to communicate with other individuals, therefore language is a very importantcomponent in our lives. The language used by someone in a different area must have differences, such as differences in language dialects. Not only in every region that experiences language differences, but also in a small community of speech communities such as the environment of a female Islamic boarding school. the environment of this Islamic boarding school narrows itself through the understanding of society, that Islamic boarding schools are a place used to pursue in-depth religious knowledge, especially for women. Basically, with the times, inthe current Islamic boarding school environment, they don't just teach religious knowledge, because many other Islamic boarding schools under their auspices have established public schools. So it's not just studying religion but general knowledge is also taught there. The development of Islamic boarding schools that have established public schools has an impact on the number of Islamic boarding school students who are not limited to one area, but also in various regions. The diversity of students and the background of the Islamic boarding school which is known to be religious which is oriented towards the large use of Arabic also has an impact on the use of language in the Islamic boarding school environment, especially in greeting words. Pondok Pesantren Putri Walisongo Jombang is one of the huts that has a specific address for the words used. The diversity of greeting words is influenced by the difference in the status of the students or santri who take shelter in the pondok as well as the Kiai and Mrs. Nyai. The students at the Islamic boarding school are divided into servant students, ordinary students and village students. The diversity of the use of language and greeting words cannot be separated from the influence of the environment and also the background of the speakers. Differences in language use caused by speakers' backgrounds and social environment will be studied through sociolinguistic studies. Through sociolinguistic studies, it was found that the diversity of greeting words used in female Islamic boarding schools, namely using a variety of Arabic, Javanese, Indonesian, and Sundanese, both in formal and non-formal contexts.